Between horror and mess: The oposition to military governments by the view of Carlinhos de Oliveira at the book Um novo animal na floresta (1968-1981) - Souza Silva, Jean Carllo de; Silva, Marcia Pereira da [UNESP] (Univ Estadual Londrina, 2015)
This article mentions the book named Um novo animal na floresta novel whose author is the chronicle writer Jose Carlos de Oliveira. By means of Carlinho's adventures, the author, called by the same name, wonders about the tension of some people who lived between the 60's and the 70's of the 20th century in environments which propitiated the support of guerrilha, but these one sopted not to be part of any group, nor left parties nor right-wing parties.
Keywords: Military dictatorship; Guerrilha; Novel; Chronicle; Writer; Literature